Radiotherapy-based conditioning is effective immunosuppression for patients undergoing transplantation with T-cell depleted stem cell grafts for severe aplasia. - Novitzky, N; Thomas, V; Stubbings, H; Hale, G; Waldmann, H (2004)
BACKGROUND: We studied the outcome of individuals with aplastic anemia conditioned with a radiation-containing regimen followed by an infusion of stem cell grafts that had been depleted of lymphocytes with CAMPATH-1H (antiCD52; humanised). METHODS: The conditioning regime consisted of fractionated (f) TBI 8 Gy followed by f total nodal irradiation (TNI) 6 Gy. In addition, patients received CY 60 mg/kg on 2 consecutive days. Cytokine-mobilized peripheral blood grafts from HLA-identical siblings were T-cell depleted with CAMPATH-1H 'in the bag'. CsA was commenced on day -1 and continued until day +90. RESULTS: Seventeen heavily transfused patients with aplastic anemia, median age 18 years (range 14-56 years), were studied. The median time from diagnosis to transplantation was 172 days (range 34-443 days). The median CD34(+) cell number infused was 3.47 x 10(6)/kg (range 1.03-18.4 x 10(6)/kg). All patients engrafted. Recovery was fast and patients reached 0.5 x 10(9)/L polymorphs by median day 11 (range 9-17 days). Toxicity from the conditioning included grade 4 hematologic toxicity in all patients. Another major toxicity was gastrointestinal mucosal damage, which exceeded grade 2 in two instances. One patient developed thrombotic thrombocytopenic purpura, which responded to substitution of CsA with tacrolimus and plasmapheresis. Another patient, who had normal blood counts, died of infection on day 241. Chimerism studies at 6 months post-transplantation confirmed the donor origin of hematopoiesis in all seven patients tested. None of the patients developed acute or chronic GvHD. There was no delayed graft failure and 94% of patients had survived disease free at a median of 1303.5 days (range 216-2615 days) from graft infusion. DISCUSSION: In this cohort of multiply transfused patients, the radiation-containing schedules described in this study led to universal engraftment with limited toxicity despite T-cell depletion. No patient developed GvHD or late graft failure. Lower doses of radiation-containing conditioning should be explored further.